Complementary n‐Type and p‐Type Graphene Films for High Power Factor Thermoelectric Generators. (25th May 2020) - Novak, Travis G.; Kim, Jin; Kim, Jungmo; Tiwari, Anand P.; Shin, Hosun; Song, Jae Yong; Jeon, Seokwoo
Abstract: Solution‐phase exfoliated graphene has always been an attractive material for flexible thermoelectric applications, but traditional oxidative routes suffer from poor flake quality and a lack of quality doping techniques to make complementary n‐type and p‐type films. Here, it is demonstrated that by changing the adsorbed surfactant during the intercalation‐exfoliation process (polyvinylpyrrolidone for n‐type, pyrenebutyric acid for p‐type), both extremely high electrical conductivity (3010 and 2330 S cm −1 ) and high Seebeck coefficients (53.1 and −45.5 µV K −1 ) can be achieved. The result is that both of these films show remarkable power factors, over 600 µW m −1 K −2 at room temperature, which is over an order of magnitude better than that in previous works demonstrating complementary n‐type and p‐type graphene thermoelectric films. Based on these films, a full all‐graphene thermoelectric device is constructed as a proof of concept, where a peak power of 5.0 nW is recorded at a temperature difference of 50 K. Abstract : Solution‐phase exfoliated graphene has the potential to be a flexible, non‐toxic, and elementally abundant thermoelectric material, but is typically limited by its poor power factor and lack of effective doping strategies. Here, non‐oxidized graphene flakes with adsorbed dopants are shown to produce extremely high power factors for both n‐type and p‐type sides of a thermoelectric device.